A phase II study of sequential decitabine and rapamycin in acute myelogenous leukemia. (January 2022) - Liesveld, Jane L.; Baran, Andrea; Azadniv, Mitra; Misch, Haley; Nedrow, Katherine; Becker, Michael; Loh, Kah Poh; O'Dwyer, Kristen M.; Mendler, Jason H.
Highlights: The majority of AML patients have constitutive activation of the PI3K/AKT/mTOR signaling pathway at diagnosis. A phase 2 study of sequential decitabine followed by the mTOR inhibitor, rapamycin was not superior to decitabine alone in terms of overall response rates. In older, newly diagnosed patients, the CR plus CRi rate was 50 % which was significantly higher than reported with decitabine alone but inferior to that reported with azacitidine and venetoclax. Non-hematologic toxicities were comparable to those with expected with decitabine alone but most patients had significant cytopenias during study duration. The role that PI3K/AKT/mTOR pathway inhibitors might play in relapsed/refractory AML continues to be examined. Abstract: A phase II study was conducted to ascertain whether sequential exposure to decitabine followed by rapamycin, an mTOR (mechanistic target of rapamycin) inhibitor would result in better responses than decitabine alone. Newly diagnosed acute myelogenous leukemia (AML) patients who were >65 years old and not eligible for intensive induction regimens or patients with relapsed or refractory AML received 10 days of decitabine followed by 12 days of rapamycin in cycle 1 and 5 days of decitabine followed by 17 days of rapamycin in subsequent cycles. The composite complete remission rate (CR) was 33 % (CR plus CR with incomplete count recovery). Median overall survival was 7.7 months in newly diagnosed elderly AML patients and 6.6 months in relapsed/refractory AML patients. Twenty-four evaluable patients were enrolled, and the study did not meet its primary endpoint of demonstrating a significant improvement in composite CR rate with the combination as compared to an established historical CR rate of 25 % with decitabine alone. Despite that, the survival rates in relapsed/refractory cases appear comparable to what is reported with other salvage regimens, and no significant patterns of non-hematologic toxicity were noted. 50 % of subjects in the de novo group achieved a composite CR which is significantly higher (p = 0.02) than the rate of 25 % with decitabine alone. This trial is registered at clinical trials.gov as NCT02109744.